Tryptophan residue is identified in the substrate binding of penicillin G acylase from Kluyvera citrophila - Kumar, R. Suresh; Prabhune, Asmita; Pundle, A. V.; Karthikeyan, Muthukumarasamy; Suresh, C. G. (Enzyme and Microbial Technology, 2007)
Penicillin acylases are important enzymes in pharmaceutical industry for the production of semi-synthetic beta-lactam antibiotics via the key intermediate 6-aminopenicillanic acid. The penicillin G acylase purified from Kluyvera citrophila (KcPGA) on modification with tryptophan-specific reagents such as N-bromo succinamide (NBS) and 2-hydroxy 5-nitrobenzylbromide (HNBB) showed partial loss of activity and substrate protection. Various solute quenchers and substrate were used to probe the microenvironment of the putative reactive tryptophan through fluorescence quenching. Homology modeling of KcPGA structure has been carried out. Docking substrate on this modeled KcPGA structure identifies the tryptophan residue that is directly influenced by substrate binding. To confirm the biological significance of this particular tryptophan, we did a sequence comparison of PGAs from various organisms. The sequence alignment clustered the matches into two sets, those closer to (> 40% identical) KcPGA and had the tryptophan of interest present in them formed the first set, while those less identical (< 30%) to KcPGA and the particular tryptophan absent in them formed the second set. It is clear from the reported kinetic parameters of representative members of these two sets that the affinity for penicillin G (penG) of the former class is several times better. Thus, based on our studies we suggest that the tryptophan residue in the identified position is important for binding substrate penG by the acylases. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: fluorescence measurement; K. citrophila; Penicillin G acylase; sequence alignment; substrate-docking; tryptophan modification